1992
DOI: 10.1108/03090599210008626
|View full text |Cite
|
Sign up to set email alerts
|

Research Report: Hospitality Graduate and Diplomate Labour Market Experiences

Abstract: The labour market experience of graduates and diplomates is a subject currently being explored in the United Kingdom. Reports on the findings of a study undertaken in Northern Ireland with special reference to the hospitality industry. Examines graduate and diplomate opinions on the preparatory value of hospitality management courses and their perception of job quality. Found that graduates in particular feel overqualified because of a lack of opportunity to implement their knowledge and skills acquired and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…There were many evident discrepancies between the perceptions of pre-work experience students and the actual experience indicating that the benefits are not being fully realised. For many students it failed to provide the range of experience they were hoping for, or at least anticipated gaining; results which are comparable with the other studies (Little and Poole, 1989;Orr et al, 1992;Purcell 1993). These variances may in part be due to departments failing to inform students accurately as to what to expect from various placement opportunities.…”
Section: Study Twosupporting
confidence: 75%
See 1 more Smart Citation
“…There were many evident discrepancies between the perceptions of pre-work experience students and the actual experience indicating that the benefits are not being fully realised. For many students it failed to provide the range of experience they were hoping for, or at least anticipated gaining; results which are comparable with the other studies (Little and Poole, 1989;Orr et al, 1992;Purcell 1993). These variances may in part be due to departments failing to inform students accurately as to what to expect from various placement opportunities.…”
Section: Study Twosupporting
confidence: 75%
“…Employers often appeared to be more interested in what the student could do on arrival rather than what he/she may be able to offer in terms of knowledge (Roy, 1988;Orr et al, 1992) or be able to do in the future. This view is reinforced by the lack of induction for most students, absence of work experience programmes and general levels of remuneration ± often less than £150 per week.…”
Section: Is Industry Maximising the Benefits?mentioning
confidence: 99%
“…This is in contrast to the "mechanistic and instrumental" learning style that Lashley identifies from recent research as typical of a new entrant onto a third level hospitality course. Orr et al (1992) suggest that, as the emphasis in the industry is learning on the job, then many of the benefits of a graduate education will be forgotten or lost by the time the graduate makes his or her way up to a management position. Groschl and Barrows (2003) in comparing French and British approaches, however, found that education does influence management style.…”
Section: Introductionmentioning
confidence: 99%
“…Wide discrepancies between perception and reality suggests that for many students, SWE failed to provide the range of experience they were hoping to gain (see Orr et al, 1992;Purcell, 1993). A significant point is the difference between perception and reality in gaining supervisory/managerial experience.…”
Section: Are Students Gaining Recognized Benefits?mentioning
confidence: 99%
“…"Unit" managers may be more interested in what the student/trainee can do now than what he or she may be able to offer in terms of knowledge (Orr et al, 1992;Roy, 1988), or may be able to do in the future. Senior personnel, however, may take a long-term view.…”
Section: Is the Industry Maximizing Benefits?mentioning
confidence: 99%